Pengaruh Ukuran Perusahaan, Solvabilitas, Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Pt. Adira Dinamika Multi Finance Tbk. Periode 2015-2024) - Rizal Abdurahman Sayuti; Nani Rusnaeni (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the effect of firm size, solvency, and profitability on firm value at PT Adira Dinamika Multi Finance Tbk during the period 2015 - 2024. Firm value is an important indicator that reflects company performance as well as investors’ perceptions of future prospects and business sustainability, and therefore serves as a basis for investment decision-making in the capital market. This research employs a quantitative method with a descriptive and verificative approach. The population of this study consists of all annual financial statements of PT Adira Dinamika Multi Finance Tbk published during the period 2015–2024. The data used are secondary data in the form of annual financial statements obtained from the official website of the company. The data analysis techniques include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results indicate that partially, firm size has a positive and significant effect on firm value, calculated tvalue > ttable (2,886 > 1,89458) means Ho is rejected and Ha is accepted, with a significance level of 0,028 < 0,05. Solvency has a positive and significant effect on firm value, calculated tvalue > ttable (2,998 > 1,89458) means Ho rejected and Ha is accepted, with a significance level of 0,024 < 0,05. Profitability has a positive and significant effect on firm value, calculated tvalue > ttable (3,421 > 1,89458) means Ho rejected and Ha is accepted, with a significance level of 0,014 < 0,05. Simultaneously, firm size, solvency, and profitability have a significant effect on firm value, calculated Fvalue > Ftable (19,174 > 4,76) with significance 0,002 < 0,05, means Ho rejected and Ha accepted. These findings indicate that companies with a larger business scale, a healthier capital structure, and a stronger ability to generate profits tend to have higher firm value in the eyes of investors